The Migratory Phenomenon in Italy- Access to Health Services - Ambrosio Silvia; Mango Lucio (Journal of Public Health International, 2020)
This article describes access to health services among migrants in Italy, summarizing barriers, policy context, and recommendations to improve equitable care.
Keywords: Immigration